Unveiling the complexity of the maize transcriptome by single-molecule long-read sequencing - Bo Wang (Nature Portfolio, 2016)
Zea mays is an important crop species and genetic model but uncertainties remain regarding the structure of the transcriptome. Here Wang et al. use single-molecule sequencing and size-fractionated libraries to identify novel transcripts and isoforms illustrating the complexity of maize mRNA.